Evaluation of relationship between anthropometric measurements and occlusal vertical dimension as an aid to determine occlusal vertical dimension in South Indian population - Gunaseelaraj, Rajkumar; Somasundaram, Santhakumari; V, Santhosh Kumar; Krishnamoorthi, Divya; Sathiyariya, S; Jayachandran, Porkodisudha (International Journal of Psychosocial Rehabilitation, 2020)
ABSTRACT-Vertical relation or vertical dimension refers to the degree of separation between the mandible or lower jawbone and the maxillae or upper jaw-bone. Craniofacial measurements play an important role in determining the vertical dimension of occlusion. To evaluate the relationship between various anthropometric measurements and occlusal vertical dimension to aid in determination of occlusal vertical dimension. A total of 200 adult South Indian subjects (100 male and 100 female) in the age group of 21 –50 years were randomly selected. The 12 variable measurements recored were Horizontal distance between pupils, Vertical distance from the pupil to Stomion, Vertical distance from the eye brow to ala of the nose, Vertical length of the nose at midline, Horizontal distance from one corner of the lip to the other, Distance between eyebrow to hairline, Distance between outer corner of one eye to inner corner of other eye, Vertical height of the ear, Distance between tip of the thumb and the tip of the index , The distance between the outer canthus of eye and Middle tragus of ear, Twice length of one eye, Twice the distance between inner canthus of both eyes, The distance between the outer canthus of eye and Middle tragus of ear and occlusal vertical dimension. Results: There was a definite relationship between the VDO and seven of the anthropometric measurements such as the horizontal distance between the pupils, eye brow to ala, pupil to Stomion, eye brow to hair line, distance between outer corner to inner corner of the eye, twice the length of the eye, the distance between the outer canthus to the ear in both the sexes. In addition to the seven measurements, Chelion to Chelion in males and vertical distance of the nose at midline for females were statistically significant. Highly significant values for males were the horizontal distance between the pupils, pupil to Stomion and the distance between the eye brow to hairline.Highly significant values for females were the horizontal distance between the pupils, pupil to Stomion and the distance between outer canthus of the eye to the ear. The sex variation was statistically significant showing a higher value for males than the females for all the twelve anthropometric measurements made. Conclusion: Anthropometric measurement found in this study can be used to cross check the OVD obtained by other means during the jaw relation procedures for determining the vertical dimension during denture construction procedure.